2021
DOI: 10.1155/2021/1586388
|View full text |Cite
|
Sign up to set email alerts
|

On the Finite Element Model of Rotating Functionally Graded Graphene Beams Resting on Elastic Foundation

Abstract: Rotating structures can be easily encountered in engineering practice such as turbines, helicopter propellers, railroad tracks in turning positions, and so on. In such cases, it can be seen as a moving beam that rotates around a fixed axis. These structures commonly operate in hot weather; as a result, the arising temperature significantly changes their mechanical response, so studying the mechanical behavior of these structures in a temperature environment has great implications for design and use in practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Based on the trigonometric HSDT, Narayan et al 32 analyzed the nonlinear vibration of curved beams. Several other investigations on the mechanical behaviors of FG‐GRC structures were reported in published works 33–37 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the trigonometric HSDT, Narayan et al 32 analyzed the nonlinear vibration of curved beams. Several other investigations on the mechanical behaviors of FG‐GRC structures were reported in published works 33–37 …”
Section: Introductionmentioning
confidence: 99%
“…Several other investigations on the mechanical behaviors of FG-GRC structures were reported in published works. [33][34][35][36][37] Moreover, there are some reports on mechanical behaviors of piezoelectric structures with graphene reinforcements. For instance, Nam et al 38 studied the nonlinear buckling of stiffened FG-GRC cylindrical panels with piezoelectric layer under axial compression.…”
Section: Introductionmentioning
confidence: 99%
“…Sylvain et al [15] established a mathematical model containing a five times nonlinear thin magnetostrictive actuator mathematical model, and it was shown that the system exhibits rich and complex dynamical properties, such as multistability and anti-monotonicity. In order to study the structural vibrations [16][17][18][19] in a system, it is essential to establish an accurate theoretical model. Nam et al [20] established a new model of beam, this new beam model is free of shear-locking for both thick and thin beams, is easy to apply in computation, and has efficiency in simulating the variable thickness beams.…”
Section: Introductionmentioning
confidence: 99%